Appraising food waste generation and forecasting food waste to energy potentials of hospitals in Turkey: A global to local analysis - Melikoğlu, Mehmet (Elsevier B.V., 2020)
Energy consumption and food waste generation from hospitals are overlooked sustainability problems. In this study, semi-empirical models based on per bed and per unit area data, and scenarios based on low, average and high food waste generation were constructed. Annual energy consumption, food waste generation and associated energy contents of food wastes produced from Turkish hospitals were estimated using these semi-empirical models and scenarios. It was found that Turkish hospitals could have consumed nearly 8600 GWh of energy in 2018. This is equal to 3.3% of Turkey's annual electricity consumption in the same year. It was calculated that nearly 49,000 tonnes of food waste could have been generated from Turkish hospitals in 2018. This amount of food waste has an energy content worth nearly 1.00% the probable energy consumption of Turkish hospitals in the same year. © 2020 Elsevier B.V., All rights reserved.
Keywords: City hospitals; Energy consumption; Modelling; Sustainability; Waste to energy